1056 Exploring the Impact of a Sleep Enhancement Program in the Inpatient Environment on Patient Satisfaction: Lessons Learned. (27th April 2018) - Moore, W R; Stellpflug, C; Ashbeck, R; Cutshall, S; Klevin, K; Marsh, S; Olson, E J; Morgenthaler, T I; Lim, K G
Abstract: Introduction: Patients experience disturbed and poor quality sleep during hospitalization that correlates with negative outcomes and poor patient satisfaction. We report outcomes from focused sleep enhancement interventions on a medical inpatient unit. Methods: Based upon sleep improvement opportunities identified via patient survey, we implemented a project with two principle aims (1) Develop a standard "sleep rounding" process to anticipate and meet patient's individual sleep preferences, and (2) improve the competency of the care team to address sleep complaints via specific sleep education and enhancement protocols. Five interventions were designed and then underwent Plan, Do, Study, Act (PDSA) cycles. These included: a sleep enhancement video viewed upon admission, a sleep enhancement menu/whiteboard, poster highlighting sleep enhancement items in hallway, workflow adjustments to minimize disruption of sleep, and a staff sleep education program. The program effectiveness was evaluated via pre-discharge patient-completed surveys. In addition, a survey was completed by staff implementing the project. Results: 80 patients completed surveys after final version implementation. 99% of patients endorsed receiving the sleep enhancement interventions. Of these, 96% felt the sleep menu was helpful. The most requested interventions included warm blankets, guided imagery, aromatherapy, backrubs, and fans. 30% of patients utilized television or tablet in addition to sleep menu offerings. Nurse survey (N=16) results reflected 69% felt the sleep enhancement offerings were beneficial and 38% perceived a reduction in call lights or patient complaints about sleep. Conclusion: The sleep education video and enhancement menu was well received by patients. Patients were resistant to trying unfamiliar sleep enhancement techniques during acute hospitalization, often reverting to coping utilized for sleep at home. Patient satisfaction was positive with the program even if sleep quality was perceived as poor. This implies focused interventions to promote sleep can be drivers to patient satisfaction during hospitalization, possibly even if sleep quality remains suboptimal. Support (If Any): The authors express gratitude to the Mayo Center for Innovation (CFI) which funded the project via a CoDE Innovation Award.